POLA KOMUNIKASI KELUARGA DALAM PERSPEKTIF ISLAM - Susanto, Agus (Jurnal Ilmiah Al-Hadi, 2020)
In the changing atmosphere of society today, families with Islamic cultural backgrounds often clash with the new values brought about by the new social system. The problem in educating teenagers is inevitable. In this case the need for certain knowledge in building effective family communication patterns so as to be able to deliver teenagers who have good emotional development. In this case parents are confronted between cultural values that are still maintained with new cultural values. His opinion quoted Friendly which explained that family communication is the readiness to speak openly to every thing in the family both pleasant and unpleasant, and also ready to solve problems in the family with conversations that are lived with patience and honesty and openness. From this, it can be understood that family communication can be established to provide something that can be given to every other family member, so that with this communication problems that occur between family members can be discussed by taking the best solution.